Optimization Design of a Real-time Embedded Operating System Based on ISO17356 - Jiang Chun-mao; Qu Ming-Cheng; Wu Xiang-hu Hu (Institute of Advanced Engineering and Science, 2013)
This paper distinguishes the differences between dynamic and static operating system from the design target, and discusses the resulting different technologies used when system is implemented. Based on this theory, according to ISO17356 OS specification and using the hardware abstraction layer idea, a simple and efficient static real-time operating system is implemented for ARM architecture, and the kernel contains no more than 3000 lines C codes. With the idea of separating mechanisms and strategies, the internal resources are used as a mechanism to implement different scheduling policies; proposes a priority-based packet scheduling algorithm, which achieves a good performance both in time and space. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3405